BEHAVIOR AND FACTORS AFFECTING THE DECISION TO PURCHASE SAFE VEGETABLES PRODUCTS THROUGH E-COMMERCE AND MULTI-CHANNEL MARKETING OF CONSUMERS IN BANGKOK METROPOLITAN AND THE VICINITIES - Rittiboonchai, Wisit (RMUTT Global Business and Economics Review, 2021)
This research aims to study 1) Decision to buy safe vegetable products through electronic commerce and multi-channel marketing by personal factors 2) Factors affecting decision to buy safe vegetable products through electronic commerce and multi-channel marketing and 3) Guidelines for developing safe vegetable purchase decisions through electronic commerce and multi-channel marketing by using integrated research. Data was collected from 750 consumers of safe vegetable products through electronic commerce and multi-channel marketing in Bangkok and its vicinities. There were 3 key informants of safe vegetable products in Bangkok and its vicinities. In additional, content validity and reliability of questionnaire and structured interviews were applied in this research. The research results were found that: 1) The decision process to buy safe vegetables had multi-channel marketing. Differences were found both in overall and in terms of factors which was classified by personal factors such as age, status, education, income and occupation. 2) Safe vegetable purchasing decisions through multi-channel marketing was caused by the overall influence of the electronic marketing mix (TE = 0.78), but technology acceptance was caused by the overall negative influence (TE = -0.36) in statistically significant. It had a predictive power of 90 percent. 3) Guidelines for safe vegetable purchase decisions development through electronic commerce and multi-channel marketing, entrepreneurs must understand the differences of buyers with those who use the application to purchase that each group. Entrepreneurs must adapt for changing situations and trends in order to accept more technologies in a new way of life.